Ethnic hospitality marketing : authenticity and quality constructions in the Greek food industry - Chatzopoulou, Elena (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Ethnic-themed restaurants are informal but powerful ambassadors for a country's culture and contributors to local and national economies. Communicating authenticity and quality are essential characteristics in the development of a competitive and effective marketing strategy for restaurants. This book analyses how authenticity and quality perceptions are both constructed and communicated within the ethnic dining sector. Drawing on qualitative research methods, the book explores examples from the Greek food industry to analyse restaurateurs' and consumer constructed meanings of authenticity, how it is transmitted and received. It follows by exploring the marketing implications of consumer constructs and effective promotional methods to aid restaurateurs to better engage with customers whilst also respecting their culinary culture. It also guides the reader through the use of NVivo for research purposes, and its utilisations to facilitate the inductive and interpretive analysis. This book offers a valuable resource for researchers across marketing, including consumer behaviour, food marketing, marketing research and communications. The data analysis tools explored are also transferable to a wide range of sectors outside of food and dining"--
Keywords: Restaurants -- Marketing; Ethnic restaurants -- Management; Food industry and trade -- Marketing -- Case studies; Food -- Greece; Greeks -- Ethnic identity; Authenticity (Philosophy); BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Consumer Behavior; BUSINESS & ECONOMICS / Marketing / General